Guaranteed upper and lower bounds on the uniform load of cont act problems in elasticity - Goriely, A; Mihai, L (Society for Industrial and Applied Mathematics, 2016)
Two mathematical models are developed within the theoretical framework of large strain elasticity for the determination of upper and lower bounds on the total strain energy of a finitely deformed hyperelastic body in unilateral contact with a rigid surface or with an elastic substrate. The model problems take the form of two continuous optimization problems with inequality constraints, the solutions of which are used to provide an enclosure on the uniform external load acting on the body’s surface away from the contact zone.